2010
DOI: 10.1007/s00726-010-0682-4
|View full text |Cite
|
Sign up to set email alerts
|

Modern developments in mass spectrometry of chondroitin and dermatan sulfate glycosaminoglycans

Abstract: Chondroitin sulfate (CS) and dermatan sulfate (DS) are special types of glycosaminoglycan (GAG) oligosaccharides able to regulate vital biological functions that depend on precise motifs of their constituent hexose sequences and the extent and location of their sulfation. As a result, the need for better understanding of CS/DS biological role called for the elaboration and application of straightforward strategies for their composition and structure elucidation. Due to its high sensitivity, reproducibility, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 81 publications
0
38
0
Order By: Relevance
“…Soft ionization mass spectrometric techniques such as MALDI or ESI are convenient methods to investigate the molecular weights of oligosaccharides [28]. We will focus here on MALDI MS because this method is influenced to a lesser extent by sample impurities, particularly the salt content.…”
Section: Resultsmentioning
confidence: 99%
“…Soft ionization mass spectrometric techniques such as MALDI or ESI are convenient methods to investigate the molecular weights of oligosaccharides [28]. We will focus here on MALDI MS because this method is influenced to a lesser extent by sample impurities, particularly the salt content.…”
Section: Resultsmentioning
confidence: 99%
“…Taking place in narrow-bore capillaries, CE allows application of a high electric field, which leads to an unsurpassed separation efficiency and resolution, a high analysis speed, reproducibility of experiments, ease of automation, and miniaturization. CE performance in glycomics was lately significantly improved by online coupling to ESI MS. By online CE/ESI MS technique, employing modern high-resolution MS instruments, molecular masses of glycoforms separated by CE can be directly measured with excellent accuracy and sensitivity; hence, a straightforward identification of single components in complex mixtures originating from biological matrices is possible [83][84][85][86]. Several reports [87][88][89] and reviews [85,82,[90][91][92][93][94] demonstrated that an effective transfer of the sample from the CE capillary into MS without affecting the separation requires an adequate optimization of the CE/ ESI interface and online working conditions in terms of: (i) the choice of an electrolyte compatible with the electrospray process; (ii) the range of the applied CE and ESI voltages; (iii) electrolyte type, concentration, and pH; (iv) sample preparation prior to analysis; (v) injection time and pressure; and (vi) capillary temperature.…”
Section: Ce-msmentioning
confidence: 99%
“…However, numerous difficulties encountered in the MS analysis of CS/DS [21][22][23][24][25][26][27] limit the benefits of this technique when applied to complex mixtures, if no separation is employed prior to MS. When the depolymerization is performed by lyases, chains of variable lengths and degrees of sulfation are formed.…”
Section: Introductionmentioning
confidence: 98%